AN OVERVIEW OF ANTI-INFLAMMATORY, ANTIOXIDANT, ANTI-CANCER, ANTI-HYPERLIPIDEMIC, NEUROPROTECTIVE AND MUSCLE RELAXANT EFFECTS OF NATURAL FLAVONOID, APIGENIN; A REVIEW - AZEEM, M; KHARL , HAA; NIAZI, S; AMEER, N; FAYYAZ, F; HUDA , NU; ZEHRA , T; AFTAB , M (Biological and Clinical Sciences Research Journal, 2024)
Apigenin (4′, 5, 7,-trihydroxyflavone), a natural glycoside belonging to a class of cyclone, is found in many different forms in plants and vegetables such as grapefruits, parsley, onions, oranges, tea, chamomile, wheat, sprouts, oregano, artichokes and in some seasonings. It effectively treats various anti-inflammatory disorders because it is less toxic, non-mutagenic, and potent against skeletal muscle sarcoplasmic reticulum. Furthermore in combination with allopathic drugs, its activity was enhanced as an anti-inflammatory, antioxidant, cardioprotective, neuroprotective, and anticancer agent. Little data was found that emphasized its role as an anti- hypoglycemic and sedative agent; however, it was found to promote hair growth by inhibiting the TGF-B1 pathway. Different characterization techniques were used to determine physicochemical properties, and various formulations of apigenin with other polymers have been done to enhance its biological role. The literature search used various scholarly search engines (Google Scholar, PubMed, Springer Link, etc.). A total of 355 research articles were reviewed, and it was observed that 34% of articles were about anti-inflammatory, 15% of articles were about neuroprotective, and 10% of studies were about anti-cancer use of apigenin. Thus, the current review focuses on its activity, characterization and limitations of apigenin role.